PENGARUH WTH TERHADAP KUALITAS AIR PADAPRE-TREATMENT AIR BERSIH MENGGUNAKAN MEDIA LIMBAH PLASTIK AIR MINUM DALAM KEMASAN (AMDK) DENGAN FIXED BED REACTOR - Mega Ayu Yusuf (AGRICOLA, 2014)
In big cities, quality of raw water (river water) is decreasing, as result of industrial and domestic wastes discharge into river without any treatment. Therefore, pre-treatment is needed to improve the raw water quality. An alternative for pre-treatment of the raw water is fixed bed reactor (FBR) system, in which organic substances can be removed biologically.In this experiment, an FBR was used to reduce concentrations of organic, ammonia, total suspended solid (TSS), color and turbidity in raw water. One type of media were used namelyrecycled plastic bottled of drinking water. The system is equipped with circulator and aerator to support the microorganism growth on the media surface as biofilms.The experiments were conducted at HRT (Hydraulic Retention Time) between 1–4 hours. HRT of 3 hours was found to be optimum for the reactor with recycled plastic bottled of drinking water with removal efficiency of organic, ammonia, total suspended solid (TSS), color and turbidity are 70%, 61%, 66%, 67% and 63% respectively.